COVID-19, mobility, leisure, and travel around the world. (15th March 2023) - Mertzanis, Charilaos; Papastathopoulos, Avraam; Koutra, Christina; Marashdeh, Hazem
Abstract: The paper uses daily data from Google to analyze the impact of the COVID-19 pandemic on people's mobility around the world regarding three types of leisure and travel activity: retail shopping and recreation; participation in open spaces, such as parks, beaches, gardens, and marinas; and food and medicine. These types of activity reflect important leisure and travel choices of people under conditions of epidemiological risk. We use the daily mortality rate as a key predictor. The results show that higher rates of mortality are associated with a lower mobility in shopping and recreation activities, higher mobility in open space activities, and rather insignificant changes in mobility regarding necessities. The effect depends on the stringency of the lockdown policies. The results remain robust after applying endogeneity analysis and country-level controls.